2004
DOI: 10.5194/acp-4-1007-2004
|View full text |Cite
|
Sign up to set email alerts
|

Gas-particle interactions above a Dutch heathland: II. Concentrations and surface exchange fluxes of atmospheric particles

Abstract: Abstract. Size-dependent particle number fluxes measured by eddy-covariance (EC) and continuous fluxes of ammonium (NH -N dry deposition amounts to 20% of the dry input of NH 3 -N over the measurement period. These surface exchange fluxes are analyzed together with simultaneous gas-phase flux measurements for indications of gas-particle interactions. On warm afternoons the apparent fluxes of acids and aerosol above the heathland showed several coinciding anomalies, all of which are consistent with NH + 4 evapo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
95
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(96 citation statements)
references
References 57 publications
1
95
0
Order By: Relevance
“…Nemitz et al, 2004a;Brost et al, 1988;Huebert et al, 1988). However, as long as the characteristic time scale of chemical transformation is large in comparison to the turbulent timescale, fluxes of compounds that underlie rapid chemical transformation may be determined with sufficient accuracy when treating them as not-reactive (De Arellano and Duynkerke, 1992;Nemitz et al, 2004b). Photochemical reactions involving NH 3 and HNO 3 are slow compared to turbulence; however, timescales of phase changes within the NH 3 -HNO 3 -NH 4 NO 3 triad (see Reaction R1), may be comparable to characteristic times of turbulent transport (Trebs et al, 2006).…”
Section: Aerodynamic Gradient Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nemitz et al, 2004a;Brost et al, 1988;Huebert et al, 1988). However, as long as the characteristic time scale of chemical transformation is large in comparison to the turbulent timescale, fluxes of compounds that underlie rapid chemical transformation may be determined with sufficient accuracy when treating them as not-reactive (De Arellano and Duynkerke, 1992;Nemitz et al, 2004b). Photochemical reactions involving NH 3 and HNO 3 are slow compared to turbulence; however, timescales of phase changes within the NH 3 -HNO 3 -NH 4 NO 3 triad (see Reaction R1), may be comparable to characteristic times of turbulent transport (Trebs et al, 2006).…”
Section: Aerodynamic Gradient Methodsmentioning
confidence: 99%
“…For particles with mean diameters of 0.25, 0.71 and 2 µm, v d at the encountered wind speeds would theoretically range between 0.01-0.6, 0.01-1.08, and 0.06-3.5 cm s −1 , respectively (Peters and Eiden, 1992). According to Gallagher et al (1997) 4 and those derived from particle number flux measurements have been reported (Nemitz et al, 2004b;Thomas, 2007). These were explained by changes in the thermodynamic equilibrium towards the more rapidly depositing gaseous species between the measurement height and the vegetated surface (Fowler et al, 2009).…”
Section: Fluxes and Deposition Velocitiesmentioning
confidence: 99%
“…In addition, NH 3 deposition depends on the N status of the receiving surface, with fertilised vegetation and vegetation receiving high atmospheric N deposition inputs acting as a less efficient sink or even, in the case of fertilised vegetation, a net source of NH 3 Walker et al, 2012a). In wet regions, leaf cuticles frequently provide an efficient sink for water soluble gases (NH 3 and HNO 3 ), although the cuticular sinks for both gases can become saturated under very dry conditions, increasing the importance of stomata as an uptake pathway (Nemitz et al, 2004b). Challenges in modelling NH 3 fluxes over vegetation have been addressed in a number of papers Wu et al, 2009).…”
Section: O Hertel Et Al: Governing Processes For Reactive Nitrogen mentioning
confidence: 99%
“…surface resistance is negligible. This is probably a reasonable approximation for most situations, but emission gradients or reduced uptake rates of HNO 3 have been observed, probably due to non-zero HNO 3 surface concentrations in equilibrium with NH 4 NO 3 deposited to leaf surfaces (Neftel et al, 1996;Nemitz et al, 2004b;Zhang et al, 1994). For trace gases with negligible surface resistance, the deposition velocity is sensitive to the atmospheric resistances (R a and R b ), which over rough surfaces are usually small (5-10 s m −1 ).…”
Section: Nitric Acidmentioning
confidence: 99%
“…Moreover, aerosol acidity plays a key role in the gas-particle partitioning of species such as HCl/Cl -, HNO3/NO3 -and NH3/NH4 + , and is therefore vital for predicting lifetimes of gaseous compounds such as NH3 and HNO3 in the atmosphere (Nemitz et al, 2004;Oss et al, 1998). Further, aerosol acidity is known to affect the 5 formation of secondary organic aerosols (SOA), e.g.…”
mentioning
confidence: 99%